Tracks [videorecording (DVD)] - Wasikowska, Mia, 1989-; Driver, Adam; Bock, Rainer; Davidson, Robyn, 1950- (Starz Media, 2015)
It tells the remarkable true story of Robyn Davidson, a young woman who leaves her life in the city to make a solo trek through almost 2,000 miles of sprawling Australian desert. Accompanied by only her dog and four unpredictable camels, she sets off on a life-changing journey of self-discovery. Along the way, she meets National Geographic photographer Rick Smolan who begins to photograph her voyage.